Temp vedenija poedinka v dzjudo i ego formirovanie u dzjudoistov vysokoj kvalifikacii - Sviscev, I. D. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
The purpose of the research was the revealing of the rate of a duel of elite judokas and the definition of the approaches to the management of it. The revealing of the structure of the duel including fragments of a duel and activity of it's three subjects various in time and contents was important for the scientific novelty of the research: two wrestlers and the arbitrator that allows to expand the circle of the researches and to leave the limits of already received theoretical representations about regularities of the course of the duel. The Results of the research can be used in lectures for students of sports educational institutions, and also at planning the training process of elite judokas, who train for the crucial competitions.